2014
DOI: 10.1038/aps.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Roles of P-glycoprotein and multidrug resistance protein in transporting para-aminosalicylic acid and its N-acetylated metabolite in mice brain

Abstract: Aim: Para-aminosalicylic acid (PAS) is effective in the treatment of manganism-induced neurotoxicity (manganism). In this study we investigated the roles of P-glycoprotein (MDR1a) and multidrug resistance protein (MRP) in transporting PAS and its N-acetylated metabolite AcPAS through blood-brain barrier. Methods: MDR1a-null or wild-type mice were intravenously injected with PAS (200 mg/kg). Thirty minutes after the injection, blood samples and brains were collected, and the concentrations of PAS and AcPAS in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…4). Despite the results of a previous study indicating that inhibition of P-gp efflux caused an increased PAS concentration in the brain (22,23), our in vitro transport data found no involvement of P-gp in PAS transport. The half-life of orally administered PAS is reported to be 1.5 to 2 h, with the concentration remaining in plasma within 4 to 5 h after administration of a single conventional dose being negligible.…”
Section: Discussioncontrasting
confidence: 99%
“…4). Despite the results of a previous study indicating that inhibition of P-gp efflux caused an increased PAS concentration in the brain (22,23), our in vitro transport data found no involvement of P-gp in PAS transport. The half-life of orally administered PAS is reported to be 1.5 to 2 h, with the concentration remaining in plasma within 4 to 5 h after administration of a single conventional dose being negligible.…”
Section: Discussioncontrasting
confidence: 99%
“…Both PAS and AcPAS were transported in the brain by the multidrug resistance-associated protein 1 (MRP1), a member of the superfamily of ATP-binding cassette (ABC) transporters. However, the removal or efflux of PAS from brain parenchyma into the blood was mediated by the multidrug resistance protein 1 (MDR1), also called P-glycoprotein [136]. …”
Section: Diagnosis and Clinical Interventionmentioning
confidence: 99%
“…P-gp was an important factor contributing to the occurrence of DDI [ 23 ], so it was necessary to evaluate whether the investigational drug was an inhibitor of P-gp. From Figure 3 , we observed that Dl0410 could inhibit the transport of Rho123 from the BL side to the AL side in MDCK-MDR1 cells, indicating that it was a substrate as well as an inhibitor of P-gp.…”
Section: Discussionmentioning
confidence: 99%